Microorganismos calcáreos y silíceos de la laguna “Don Tomás”, provincia de La Pampa, Argentina - Kihn, Romina Gisela (2022)
Studies on diatoms, cysts and ostracods in shallow lakes are very scarce in the Province of La Pampa. The aim of this study is to collect new information on the diversity and abundance of microorganisms present in a hypertrophic body of water and their seasonal changes. The samplings were carried out seasonally in the period from January to October 2014. From the sediment analysis of the Don Tomás lagoon, 21 diatom taxa were identified, of which three correspond to the order Centrales and 18 to the order Pennales; four genera of ostracods and two morphotypes of chrysophyte cysts (ornamented and smooth) were also recorded. The data obtained from the study of current samples will allow us to interpret with a greater degree of certainty the Holocene deposits from lake environments of temperate climates.